PENGARUH SERVANT LEADERSHIP, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU SD NEGERI DI WILAYAH PEUSANGAN KABUPATEN BIREUEN - Safwandi, Safwandi; Konadi, Win (IndOmera, 2023)
This study aims to determine the effect of Servant Leadership, Teacher Work Discipline and Job Satisfaction both partially and simultaneously on teacher performance. The research was in the form of a survey of a sample of 226 public elementary school teachers in the Peusangan area of ​​Bireuen Regency. This type of quantitative research was carried out using descriptive and associative analysis, with a path analysis model approach. The results of the path analysis show, 1) the Servant Leadership factor has a direct effect of 0.472 on teacher performance, 2) the teacher discipline factor has a direct effect of 0.312 on teacher performance, 3) the job satisfaction factor has a direct effect of 0.214 on teacher performance, 4) The servant leadership factor through discipline and teacher job satisfaction have an effect of 46.75% on teacher performance, 5) Work discipline factors through servant leadership and job satisfaction have an effect of 32.6% on teacher performance, 6). The Job Satisfaction Factor through Servant Leadership and Work Discipline influences Teacher Performance by 26.56%. 7) Simultaneously servant leadership, work discipline and job satisfaction contribute to changes in teacher performance by 57.9%. While the remaining 42.1% is influenced by other factors not examined, researchers suspect from the aspects of work motivation, teacher competence, work environment and others.